Analisis Respon Hidrologi Dengan Simulasi Hujan Terhadap Perubahan Fungsi Lahan: Studi Kasus Di Situ Cibuntu: Analysis Of Hydrological Response With Rainfall Simulation On Changes In Land Function: Study Case Cibuntu Lake - Cahyono, Afandi Wahyu; Ikhsan, Jazaul; Apip, Apip (Media Ilmiah Teknik Sipil, 2024)
Changes in land use in Indonesia are often not accompanied by land conservation measures, which causes land to become increasingly degraded, which is characterized by high erosion hazards and low levels of rainwater infiltration. To determine the impact of changes in land function, it is necessary to carry out a hydrological response analysis to determine the land's response to falling rainfall, one of which is using the rain simulator. This research was carried out by providing rain simulations on two land functions, namely on artificial forest land and open land. This research uses several hydrological parameters such as rainfall, infiltration, soil moisture, runoff and sediment yield as a comparison of the response on the two fields. The results of this research show that the change in land function from forest to open land causes changes in the hydrological response, which causes the potential for flooding due to reduced permeable land, resulting in a lot of rain running off